y = 2 * log[4](x - 3)
Switch x with y, solve for y
x = 2 * log[4](y - 3)
x/2 = log[4](y - 3)
4^(x/2) = y - 3
(2^2)^(x/2) = y - 3
2^(2x / 2) = y - 3
2^x = y - 3
y = 3 + 2^x
Switch x with y, solve for y
x = 2 * log[4](y - 3)
x/2 = log[4](y - 3)
4^(x/2) = y - 3
(2^2)^(x/2) = y - 3
2^(2x / 2) = y - 3
2^x = y - 3
y = 3 + 2^x
-
To find the inverse, let f(x) = y, interchange x and y, and re-solve for y; the resulting expression in y will be the inverse.
Letting f(x) = y:
y = 2log₄(x - 3).
Interchanging x and y:
x = 2log₄(y - 3).
Then, re-solving for y:
log₄(y - 3) = x/2, by isolating the logarithm function
==> y - 3 = 4^(x/2), by the definition of the logarithm
==> y = f^-1(x) = 4^(x/2) + 3.
I hope this helps!
Letting f(x) = y:
y = 2log₄(x - 3).
Interchanging x and y:
x = 2log₄(y - 3).
Then, re-solving for y:
log₄(y - 3) = x/2, by isolating the logarithm function
==> y - 3 = 4^(x/2), by the definition of the logarithm
==> y = f^-1(x) = 4^(x/2) + 3.
I hope this helps!
-
Assuming that the function is bijective,
Let y=f(x)=2log_4 (x-3)
y/2=log_4 (x-3)
4^(y/2)=x-3
2^(2*y/2)=x-3
2^y=x-3
x=3+2^y
if y=f(x) => x=f^-1(y)
Therefore, f^-1(y)=3+2^y
put y=x
=>f^-1(x)=3+2^x
g(x)=3+2^x is the inverse of f(x).
Let y=f(x)=2log_4 (x-3)
y/2=log_4 (x-3)
4^(y/2)=x-3
2^(2*y/2)=x-3
2^y=x-3
x=3+2^y
if y=f(x) => x=f^-1(y)
Therefore, f^-1(y)=3+2^y
put y=x
=>f^-1(x)=3+2^x
g(x)=3+2^x is the inverse of f(x).